Perancangan Aplikasi Mobile Library pada Perpustakaan Sekolah Tinggi Teknologi Bontang Berbasis Android - Hardianto; Abdul Zain (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Library is one of the supporting facilities that help in the provision of information resources in the education process, because the library provides facilities for lending books without burdened with any cost. To facilitate the process of searching and lending services by the borrower against the library, it takes a system that allows library members to access library services, especially the process of borrowing books online using aplicasimobile librarybased android. The success and development of android is currently able to occupy the highest position of the market gadgets and computers, this is certainly thanks to the sophistication of technology systems and applications that exist in it which is currently a trend among mobile phone users because it can help all areas of work so it becomes easier . The advantages of this android is located in an opensource license so it is possible for anyone who has android programming capabilities to create or develop various applications to run on android based gadgets. This application is one of the technological development that is very helpful in facilitating library services based on mobile android course with android gadget device that has been installed this application.